2010
DOI: 10.1371/journal.pone.0012106
|View full text |Cite
|
Sign up to set email alerts
|

Limited Systemic Sclerosis Patients with Pulmonary Arterial Hypertension Show Biomarkers of Inflammation and Vascular Injury

Abstract: BackgroundPulmonary arterial hypertension (PAH) is a common complication for individuals with limited systemic sclerosis (lSSc). The identification and characterization of biomarkers for lSSc-PAH should lead to less invasive screening, a better understanding of pathogenesis, and improved treatment.Methods and FindingsForty-nine PBMC samples were obtained from 21 lSSc subjects without PAH (lSSc-noPAH), 15 lSSc subjects with PAH (lSSc-PAH), and 10 healthy controls; three subjects provided PBMCs one year later. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
3
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 55 publications
13
138
3
1
Order By: Relevance
“…The database does not record the results of RHC and markers of vascular endothelial injury have not been collected (such as vascular cell adhesion molecule 1, vascular endothelial growth factor, and von Willebrand factor). The latter has been reported as being associated with SSc PAH in lcSSc (39).…”
Section: Discussionmentioning
confidence: 88%
“…The database does not record the results of RHC and markers of vascular endothelial injury have not been collected (such as vascular cell adhesion molecule 1, vascular endothelial growth factor, and von Willebrand factor). The latter has been reported as being associated with SSc PAH in lcSSc (39).…”
Section: Discussionmentioning
confidence: 88%
“…In one study of PAH lung tissue, of ϳ14,000 genes with measurable expression, 13,889 were altered (57). Among studies of PAH patient-derived samples, there have been three studies of lung tissue specimens (28,39,57), four studies of freshly isolated circulating cells (11,30,56,63), and three studies of cells cultured from PAH patients (5,24,65). While the overall results have been recently reviewed (48), we reexamined these data to determine whether they also identified alterations in expression of Wnt signaling molecules as a disease-associated signaling pathway (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…52 Furthermore, vWF has been associated with PAP greater than 40 mm Hg and to predict the future development of PAH. 73,74 In addition, one study showed that patients from the PHAROS registry with incident SSc-PAH expressed higher levels of hepatocyte grown factor than patients with SSc without definite PAH. These levels also correlated with increased RVSP on echocardiogram.…”
Section: Novel Biomarkersmentioning
confidence: 99%